Factorial analysis of the elements that compose the training in the small and medium enterprises of the Industrial sector - Vasquez-Torres, Maria del Carmen (Zielona Góra: Faculty of Economics and Management Press)
The most important factor in small and medium-sized enterprises is undoubtedly the training; intellectual capital directly impacts the growth and productivity of the organization, so the preparation given to employees is vital. The study carried out a factorial analysis to identify the components to be considered in the training of the SMEs in the industrial sector of Ciudad Obregon, Sonora, México.
Keywords: małe i średnie przedsiębiorstwo; zasoby ludzkie; analiza czynnikowa; small and medium-sized enterprises; human resources; factorial analysis; training